Differences in Student Trigonometry Learning Outcomes Using Project Based Learning and Problem Based Learning Models - Kenny E. F. Bawoleh; James U. L. Mangobi; Vivian E. Regar (Journal on Education, 2023)
This study aimed to determine differences in trigonometry learning outcomes for class XI IPA students using project- and problem-based learning models. This study uses a quantitative approach. The subjects in this study were students of class XI IPA at SMAN 1 Tondano. The data collection technique was carried out by giving post-tests to students. The results of data analysis show that learning mathematics on trigonometry material experiences several obstacles, including When learning, students tend not to pay attention, students are not much involved in interpreting their knowledge, only receive information conveyed by the teacher, students tend to forget the material quickly, students are not able to solve problems that different from the example questions, the learning model applied is less effective. In addition, in this study, there are differences in trigonometry learning outcomes between students who are taught using the PjBL model with students who are taught using the PBL model.